2022
DOI: 10.3390/coatings12060855
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated-Triazole-Modified ZnO and Its Application in Marine Antifouling

Abstract: The accumulation of marine biological growth has irreversible negative effects on shipping and coastal fisheries. In this paper, a new antibacterial nanofiller—triazole fluoroaromatic hydrocarbon−modified nano−zinc oxide (ZnO−APTES−TRF)—was prepared by a Cu(I)−catalyzed azide–alkyne click chemical reaction. The modification of nano−ZnO with triazole ring fluoroaromatic hydrocarbons were testified by FT−IR, XPS, and EDS. The grafting rate of ZnO−APTES−TRF can reach 32.38%, which was verified by the TGA test. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Triazoles are five membered heterocyclic compounds that have attracted a sustainable and increasing attention from the scientific community due to their wide applications in different fields such as pharmaceutics, 25,26 agriculture 27 as well as material sciences. [28][29][30] Among others, 1,2,4-triazole derivatives, which possess three nitrogen atoms placed at 1, 2 and 4 positions, have become extraordinarily important due to their wide-ranging antibacterial, antifungal, antitubercular, antioxidant, antitumor, analgesic, antiinflammatory or pesticidal properties. 31,32 More interestingly, these special properties can be tunable upon integrating various substituents on all the nitrogen and carbon atoms of the skeleton, thereby further facilitating the use of 1,2,4-triazoles for a broad panel of applications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Triazoles are five membered heterocyclic compounds that have attracted a sustainable and increasing attention from the scientific community due to their wide applications in different fields such as pharmaceutics, 25,26 agriculture 27 as well as material sciences. [28][29][30] Among others, 1,2,4-triazole derivatives, which possess three nitrogen atoms placed at 1, 2 and 4 positions, have become extraordinarily important due to their wide-ranging antibacterial, antifungal, antitubercular, antioxidant, antitumor, analgesic, antiinflammatory or pesticidal properties. 31,32 More interestingly, these special properties can be tunable upon integrating various substituents on all the nitrogen and carbon atoms of the skeleton, thereby further facilitating the use of 1,2,4-triazoles for a broad panel of applications.…”
mentioning
confidence: 99%
“…Many attempts have therefore been realized to either further developing of new triazole classes [33][34][35] or integrating them with other potential materials for forming novel composites so far. 30,36,37 Interestingly, covalent anchoring of 1,2,4-triazole derivatives onto solid surfaces is assigned as a promising strategy to create novel functional materials due to its two-fold effect, namely (i) full utilization of unique properties of triazoles and (ii) maximized durability of fabricated materials resulted from their robust interaction via covalent linkers. Nevertheless, there a few studies focusing on this approach have been reported so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation